Cross-channel spillover effect of price promotion in fashion. Issue 10 (29th June 2020) - Kim, Yunjeong; Lee, Yuri
Abstract : Purpose: The purpose of this study was to investigate whether consumers differ in their online or offline purchase intention, depending on which channel with price promotion information they are first exposed to, and to analyse the moderating role of brand trust. Design/methodology/approach: Overall, 174 responses were obtained via an online survey using two contact channels (online/offline) by two levels of brand trust (high/low) between-subject designs. Findings: Spillover effects were found across channels when a consistent price promotion is executed in both online and offline channels, purchase intentions for cross-channel and contact channel increase simultaneously. Although there was a similar effect in the discrepancy of purchase intentions towards the cross-channel according to contact channels, it varied depending on brand trust. When brand trust is high, having contact with offline price-discount information has a large online spillover effect. When brand trust is low, the spillover effect from online to offline is large. Research limitations/implications: This study expands the multi-channel research by proving the spillover effects between channels and confirming the difference according to brand trust. Practical implications: Increasing promotion information for online contact is effective in driving offline visits for new brands, and the effective use of promotion information at offline stores can have a positive impact on online channels for well-known brands. Originality/value: This study explores the cross-channel spillover effect of price promotion and proves that these effects depend on brand trust.